Computational fluid dynamics modelling and optimization of solar powered direct contact membrane distillation with localized heating for off-grid desalination - Samadi, Akbar; Samadi, Shahla; Di Profio, Gianluca; Zhao, Shuaifei; Fontananova, Enrica (Frontiers in Membrane Science and Technology, 2024)
Introduction: Membrane distillation (MD) is a promising technique for desalination, capable of utilizing low-grade heat. However, MD faces some challenges such as temperature polarization. To overcome these issues, direct solar MD with localized heating (LHMD) has emerged as a cost-effective and efficient solution by leveraging solar energy. Methods: This study focuses on process optimization of LHMD using computational fluid dynamics (CFD) modeling. CFD simulation was applied to investigate the fluid behavior, heat transfer, and mass transfer within the system. Several key factors, including module geometry, process configuration, solar irradiation, feed flow rate, and feed temperature are investigated. Results: The effects of these parameters on the distillate production rate, thermal behavior, and energy efficiency, are evaluated for optimization. At the optimal conditions, 1 m2 membrane in a module with a length of 50 cm and a channel height of 1.5 mm under a counter-current flow generates 12 L drinking water per day, which meets the basic drinking water demands for 6 people. Over 70% gain output ratio can be achieved when the feed temperature is more than 20°C, the feed velocity is 1–1.5 mm/s, and the feed salinity is less than 1000 mol·m−3. This setup can also produce 6 L of distilled water per day when a water with a salinity six times higher than seawater if the feed velocity is sufficiently low. Discussions: The main feature of the localized heating is the reverse temperature polarization on the feed side, leading to the increase in energy efficiency and the ease of scale-up.